Micro-propagation of Plus Neem (Azadirachta indica A. Juss) and Evaluation of Field Transferred Plants - Venkateswarlu, B.; Katyal, J. C.; Choudhuri, Jayjayanti; Mukhopadhyay, K. (Indian Forester, 1998)
A micro-propagation protocol for a mature plus Neem tree has been standardized. Nodal explants from actively growing young shoots of 22 year old plus tree with straight stem, 50 kg seed yield/year, 25% oil in seeds and 0.6% azadirachtin in kernels was used as mother tree to initiate the culture. Successful shoot bud induction and multiplication could be achieved on MS medium with suitable concentrations of cytokinin. Elongated shoots could be rooted in-vitro by using 2.5 mg/l of IAA, transferred to soil + vermiculite mix (1:1), and were hardened in a mist chamber in a gradually decreasing humidity regime. The hardened plants were successfully transferred into the field and data on survival per cent, height and collar diameter were recorded upto 6 months. Tissue cultured plants showed superior performance as compared to seed derived samplings.